Enablers and constraints to energy communities: lessons for energy communities in Sub-Saharan Africa - Okem, Andrew Emmanuel; Ley, D. (Routledge, 2023)
This chapter examines the negative implications of poor/limited access to energy. It also examines the meaning and characteristics of Energy Communities (ECs), followed by a review of enablers and barriers to ECs. The chapter explores some key policy recommendations that could enable the formation of ECs in sub-Saharan Africa in the region’s effort to reduce deficits concerning access to clean energy. Available evidence reveals that there has been a consistent growth in access to energy. Essentially, ECs are grassroots initiatives informed by the principles of democratic participation. They are geared towards responding to collectively agreed outcomes. The concept is associated with characteristics inherent in citizen participation, ownership, and control. Enabling policies and related government actions have been instrumental in driving the formation of and sustaining ECs. The literature identifies several barriers to renewable energy initiatives and the establishment of ECs.